Endothelial cell-derived heparan sulfate binds basic fibroblast growth factor and protects it from proteolytic degradation (The Rockefeller University Press, 1988)
Cultured bovine capillary endothelial (BCE) cells were found to synthesize and secrete high molecular mass heparan sulfate proteoglycans and glycosaminoglycans, which bound basic fibroblast growth factor (bFGF). The secreted heparan sulfate molecules were purified by DEAE cellulose chromatography, followed by Sepharose 4B chromatography and affinity chromatography on immobilized bFGF. Most of the heparinase-sensitive sulfated molecules secreted into the medium by BCE cells bound to immobilized bFGF at low salt concentrations. However, elution from bFGF with increasing salt concentrations demonstrated varying affinities for bFGF among the secreted heparan sulfate molecules, with part of the heparan sulfate requiring NaCl concentrations between 1.0 and 1.5 M for elution. Cell extracts prepared from BCE cells also contained a bFGF-binding heparan sulfate proteoglycan, which could be released from the intact cells by a short proteinase treatment. The purified bFGF-binding heparan sulfate competed with 125I-bFGF for binding to low-affinity binding sites but not to high-affinity sites on the cells. Heparan sulfate did not interfere with bFGF stimulation of plasminogen activator activity in BCE cells in agreement with its lack of effect on binding of 125I-bFGF to high-affinity sites. Soluble bFGF was readily degraded by plasmin, whereas bFGF bound to heparan sulfate was protected from proteolytic degradation. Treatment of the heparan sulfate with heparinase before addition of plasmin abolished the protection and resulted in degradation of bFGF by the added proteinase. The results suggest that heparan sulfate released either directly by cells or through proteolytic degradation of their extracellular milieu may act as carrier for bFGF and facilitate the diffusion of locally produced growth factor by competing with its binding to surrounding matrix structures. Simultaneously, the secreted heparan sulfate glycosaminoglycans protect the growth factor from proteolytic degradation by extracellular proteinases, which are abundant at sites of neovascularization or cell invasion.